EKSISTENSI HUKUM ISLAM DI TENGAH DINAMIKA PRANATA SOSIAL INDONESIA - Mundakir Mundakir (Program Studi Hukum Keluarga Islam, 2017)
The challenge in the implementation of Islamic laws that moslems in Indonesia face does not have to do with the struggle for recognition by national laws. Instead, it has to do with trying to clarify their position among various social groups. It also examine how much Islamic laws contribute values that stimulate development, order, peace and welfare for the nation and country. Historically, Qur’anic legal verses were revealed mostly after the Messenger migrated to Medina, while Meccan verses are identified as to consolidate the ummah so that they were ready to bear the burden imposed by the Islamic laws (taklif).The regulations reflecting syari’ah laws issued by the local governments and their implementation tend to be euphoric taking the chance given by the reform. They have not reflected different social groups on which the regulations will be imposed. Islamic laws as the basic consideration in formulating the local government regulations seem not to have accommodated religious elements comprehensively, i.e. integrating aqidah, akhlaq and syari’ah guiding people’s behavior conceptually as well as in practice. Therefore, partial implementation of Islamic syari’ah only will result in pseudo-religiosity, and tend to become a problem for the ummah themselves.